Inovativnost slovenskih lastnikov gozdov na začetku novega tisočletja - Šinko, Milan (Gozdarski vestnik, 2009)
The article deals with the innovatory activities of the Slovenian forest owners before 2002. It presents theoretical starting-points of the innovativeness and results of the empirical research on innovations in private forestry plants with forest surface above 10 hectares. The factors affecting the introduction of novelties in a stimulative and inhibitory way are treated.
Keywords: inovacije; forestry; gozdarstvo; lastniki